1990
DOI: 10.1136/hrt.64.6.385
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous subaortic position of the brachiocephalic vein (innominate vein): an echocardiographic study.

Abstract: In 24 (0.98%) of 2457 patients with congenital heart disease the brachiocephalic vein was in an anomalous position below the aortic arch. This is a much higher proportion of such cases than reported so far. This high frequency may arise from differences in the study population and the method of diagnosis. This venous anomaly was more common in patients with tetralogy of Fallot or ventricular septal defect with pulmonary atresia. Patients with the venous anomaly were more likely to have a right aortic arch. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 2 publications
3
61
0
Order By: Relevance
“…This aortic abnormality has been reported in ALBCV patients as high as 46% [14], 70% [19], 77% [3] and 86% [10]. In a study by Choi et al [4] it was shown that the presence of ALBCV in other congenital heart anomalies such as TOF, VSD or pulmonary atresia is associated with higher incidence of right sided aortic arch.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…This aortic abnormality has been reported in ALBCV patients as high as 46% [14], 70% [19], 77% [3] and 86% [10]. In a study by Choi et al [4] it was shown that the presence of ALBCV in other congenital heart anomalies such as TOF, VSD or pulmonary atresia is associated with higher incidence of right sided aortic arch.…”
Section: Resultsmentioning
confidence: 72%
“…High incidence of other cardiac abnormalities in these patients has been reported previously [4,6,10]. In a study published at 2010, Nagashima et al [14] reviewed surgical records of 4805 patients and found 15 patients with ALBCV.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations